178k views
1 vote
2-5(h+3)=-28 What does h equal? SHOW YOUR WORK

2 Answers

0 votes

3(x+1) = 2(x-8) + 3. First, remove the parentheses by distributing (multiplying out the numbers):


3x + 3 = 2x - 16 + 3.

Then, combine any like terms on the same side of the equals sign;


3x + 3 = 2x -13.

Then, move the like terms on opposite sides of the equals sign to the same side of the equals sign (don't forget to change the signs)..


3x -2x = -13 - 3.

Then combine the like terms on the same side of the equals sign again.. x = -16 .

User Vinhboy
by
5.8k points
2 votes
sorry if not clear on screen
2-5(h+3)=-28 What does h equal? SHOW YOUR WORK-example-1
User Tashawna
by
5.7k points